PEPTIDES, DEVICES, AND METHODS FOR THE DETECTION OF ANAPLASMA ANTIBODIES - BLEILE DENNIS M; MEHRA RAJESH K; WALKER JEREMY D; FORSYTH TIMOTHY P; ROGERS ANDREW P; CUESICO CHRISTINA R; ARON KENNETH P (2015)
The invention provides populations of isolated peptides useful for the detection of antibodies that bind to Anaplasma antigens. The peptide populations comprise peptides derived from immunogenic fragments of the Anaplasma Outer Membrane Protein proteins. The invention also provides devices, methods, and kits comprising the populations of isolated peptides useful for the detection of antibodies that bind to Anaplasma antigens and the diagnosis of anaplasmosis. Methods of identifying the particular Anaplasma species infecting a subject using the peptide populations of the invention are also disclosed.